2004
DOI: 10.1007/s00421-004-1047-z
|View full text |Cite
|
Sign up to set email alerts
|

Cold-water acclimation does not modify whole-body fluid regulation during subsequent cold-water immersion

Abstract: We investigated the impact of cold-water acclimation on whole-body fluid regulation using tracer-dilution methods to differentiate between the intracellular and extracellular fluid compartments. Seven euhydrated males [age 24.7 (8.7) years, mass 74.4 (6.4) kg, height 176.8 (7.8) cm, sum of eight skinfolds 107.4 (20.4) mm; mean (SD)] participated in a 14-day cold-water acclimation protocol, with 60-min resting cold-water stress tests [CWST; 18.1 (0.1) degrees C] on days 1, 8 and 15, and 90-min resting cold-wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Data from our laboratory (Stocks et al 2004), and others (Atterhog et al 1975;Sramek et al 1993), have demonstrated that cold exposure decreases rather than increases plasma volume. Therefore, changes in plasma volume are not likely to contribute to the observed decrease in plasma leptin concentration.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Data from our laboratory (Stocks et al 2004), and others (Atterhog et al 1975;Sramek et al 1993), have demonstrated that cold exposure decreases rather than increases plasma volume. Therefore, changes in plasma volume are not likely to contribute to the observed decrease in plasma leptin concentration.…”
Section: Discussionmentioning
confidence: 82%
“…Seven of these subjects also participated in a more extensive study, involving measurements of thermogenic responses, body-fluid compartment changes, and hormonal responses (Stocks et al 2004). The subjects acted as their own controls for this experiment, with the difference between the first and last immersion being used to evaluate the effects of chronic cold exposure.…”
Section: Study 1: Cold-water Immersionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to STOCKS et al (2004), winter swimming does not exert any effect on plasma osmolality, total serum protein and electrolyte levels, which suggests that immersion in cold water is associated with a shift of extracellular fluid to interstitial space. FR_HLICH et al 1997 shown seasonal changes in fibrinogen where maximum level was reached in April, and the seasonal difference was 0,32 g/L.…”
Section: Discussionmentioning
confidence: 99%
“…The body fluid ionic environment influences the nervous functions that maintain the dynamic balance of organisms through a series of biophysical and chemical reactions [1] , [2] , [3] , [4] . Body fluids account for approximately 60% of body weight [5] . Numerous studies have shown that maintaining electrolyte concentration inside and outside the cell in a state of dynamic balance is essential for biological activities [6] , [7] , [8] , [9] .…”
Section: Introductionmentioning
confidence: 99%